Mengembangkan Potensi Kecerdasan Spiritual Anak Usia Dini Implikasi Bimbingannya - El Fiah, Rifda (Universitas Islam Negeri Raden Intan Lampung, 2014)
Given the importance of spiritual intelligence for the individual to find the true happiness and meaningfulness of his life, educators should recognize, understand and develop this highest intelligence from an early age. With understanding and introduction from the beginning, it is hoped that the character building effort will produce a solid private building as a foundation to build more qualified Indonesian human resources